Qatari voices A celeberation of new writers - Henderson, Carol; Rajakumar, Mohanalakdhmi (Doha, Qatar (3OGQ HdheRHQj(B-(3eDSSI bWQ(B=Bloomsbury-Qatar foudations, 2010)
Qatari Voices is the first anthology that represents 25 young creative Qatari authors. The anthology reflects concerns and aspirations of the young Qatari generation illustrated in essays and stories. They are intimate glimpses of old reminiscence and longing to the simple past, as well as photos that show concerns of a challenging present and aspirations to the future. They also tackle sensitive issues such as arranged marriages and gender discrimination. "Qatari Voices" is a mirror of reality of the Qatari society from a young generation perspective
12
Keywords: Cultural Policy; Qatar -- History; Youth movement; culture